Energy-efficiency of community supported agriculture farms and conventional vegetable production - Menzel, Albrecht; Egli, Lukas; Gross, Arthur (Frontiers in Sustainable Food Systems, 2025)
Given the multiple challenges agriculture faces today, approaches that ensure both food security and the sustainable use of agroecosystems are urgently needed. The concept of community supported agriculture (CSA) is a promising attempt to address all three sustainability dimensions, but empirical research is still limited. Energy efficiency of farming systems is one important aspect when describing their ecological sustainability. This case study compares three CSA farms with three conventional farms, all focusing on vegetable production. Life cycle assessment (LCA) methodology was used to incorporate all relevant energy flows related to vegetable production, including all upstream activities from cradle to farmgate. CSA-farms showed energy return of investment (EROI) factors of 0.13–0.44, while EROI of conventional farms was between 0.02 and 0.69. Energy inputs, particularly fuels, electricity and fertilizer were major determinants, and related to size and structure of farms, while high yield could partially compensate for high energy inputs. CSA farms thereby tended to show relatively low consumption of fossil energy sources, partly due to on-farm electricity production by photovoltaic. Therefore, the performance of CSA regarding EROI of non-renewable energy sources (NRE) was relatively higher (0.17–0.76 compared to 0.05–0.78 for conventional farms). To further improve the energy efficiency, CSA farms need to improve their balance of inputs and outputs (e. g. reduced consumption of fossil fuels without compromising yields). However, CSA reached high energy efficiency if lifecycle costs of distribution were included (EROI = 0.6–3.1), which is likely to be lower in conventional farms with long supply chains and heavy processing. Moreover, CSA also provides additional ecological (e.g., fostering biodiversity, reduction of food loss and waste), social (e.g., education, transparency) and economic benefits (e.g., guaranteed sales). These benefits, as well as a more comprehensive assessment of energy efficiency of different production systems including more farms, need to be considered to better understand the potential contribution of CSA to a transformation toward sustainable food systems.